Per un’edizione critica del «Dit de l’unicorne et du serpent» (Carte Romanze, 2024)
The aim of this essay is to (re)bring to light a short allegorical tale that, like most short texts of an unidentified nature, has been included in the vast and heterogeneous 'genre' of the dit. Although not a well-known work to date, the (Dit) de l'unicorne et du serpent presents itself as an interesting narrative that lends itself to both literary and specifically ecdotal reflections. The text that has come down to us is the result of a re-elaboration of an ancient legend that, proposing the topos of the tree of life, has been transposed in various ways in the different types of texts in which it appears, produced at different historical moments and in different geographical areas. Transmitted by no less than 18 codices, the anonymous tale in scripta piccarda presents an unstable mise en écrit, characterised by a rich variety of lectio.
Keywords: transmission and reception; dit,; unicorn and serpent; the tree of life; varia lectio